Aspectos históricos, filosóficos y astronómicos de la cultura egipcia - Carvajal Mena, Ligia (2016)
The article highlights some background to the development of the Egyptian culture. Mentions various relevant aspects of this, on the basis of the first settlements and forms of social, political and economic organization until the formation of the monarchy, unification that allows commercial, cultural progress, the development of the social sectors and the formation of any religious ideology as political and economic control mechanisms reflected in the structuring of two types of calendars: the civil and religious that determine the modus Vivendi of Egyptians and later will serve as a basis for the formulation of Western calendars.